Biological bank protection: trees are more effective than grasses at resisting erosion from major river floods. Issue 5 (26th August 2014) - Rood, Stewart B.; Bigelow, Sarah G.; Polzin, Mary Louise; Gill, Karen M.; Coburn, Craig A.; Boudell, Jere A.; Dixon, Mark D.; Rood, Stewart B.; Stromberg, Juliet C.
Abstract Although it is recognized that streamside vegetation can reduce river bank erosion, the relative effectiveness of forest versus grassland has been unclear. To compare erosion resistance of the two vegetation types, we studied the free‐flowing Elk River in British Columbia, Canada from 1993 to 2014, including major floods in June 1995 and 2013. Interpretation of aerial photographs from 1994 and 2000 were used to examine the correspondence between floodplain vegetation and the extent of channel change after the 1995 flood. Along a 23 km reach with alternating forest and grassland, 15 locations displayed substantial change as the river moved a channel width (45 m) or more with meander migration, or up to 200 m with channel avulsion. All ten locations with major change (>75 m) occurred where the floodplain zones were occupied by grasslands, sometimes with small shrubs. In contrast, channels flanked by forest were minimally altered (<15 m), and deciduous (black cottonwood, Populus trichocarpa) or mixed deciduous‐coniferous groves were effective at resisting erosion. Some changes accompanied the 1995 flood and further changes followed as the destabilized banks were vulnerable to smaller floods in 1996 and 1997. Providing another comparison, a position that was dramatically scoured in 1995 when it was grassland had subsequent cottonwood colonization, and the 4 m trees resisted erosion from the 2013 flood. Thus, trees were more resistant than grassland to flood‐associated bank erosion. We recommend that riparian forests should be conserved to provide bank stability and to maintain an equilibrium of river and floodplain dynamics. Copyright © 2014 John Wiley & Sons, Ltd.